Computation of propagation characteristics in complex plane for multilayer optical waveguide - M.M. Ameen, Sabah; A. Amara, Ali (University of Thi-Qar Journal of Science, 2009)
This paper provides a numerical simulation for determining the complex propagation constants of integrated optics waveguide. The waveguide under consideration may consist of any number of layers with complex indices due to gain and loss. A general-purpose mode solver MAPLE program has been developed to implement the transfer matrix method, and then it applied to solving the multilayer waveguide dispersion equation in complex plane. Additionally, our program can be used to determine the electromagnetic mode structure including modal power, spatial distribution, mode size parameters, and the position of the modal peak power. Therefore, all necessary parameters for a wide range of laser devices can be calculated.